ANALISIS KEPUASAN USER TERHADAP WEBSITE ADI UNGGUL BHIRAWA SURAKARTA - Yusuf Sutanto; Wing Wahyu Winarno; Andi Sunyoto (STIE AUB Surakarta, 2014)
This study entitled Analysis is The User Satisfaction on Website Adi Unggul Bhirawa Surakarta. Case Study at STIE Adi Unggul Bhirawa Surakarta. The purpose of this research is to know how much value of hope than reality obtained (satisfaction) of students as a user facility of STIE Adi Unggul Bhirawa website for D3 Program at Information Management. Expectations of the results of this analysis will be used as a guide in the study program to evaluate and improve the accreditation process which is still accredited